New treatments for atopic dermatitis - Williams, Hywel (BMJ Publishing Group, 2002)
Atopic dermatitis now affects 15% to 20% of chil dren in developed countries, and prevalence in cities in developing countries undergoing rapid demographic changes is quickly following suit.1 Most cases of atopic dermatitis in a given community are mild, but children with moderate to severe disease can have continuous itching and associated loss of sleep. The social stigma of a visible skin disease can also be soul destroying for both patient and family. A few studies have suggested that some degree of prevention of the disease is possible,2 although these measures have not been taken up widely. In the absence of any treatment that is known to alter the clinical course of the disease, most treatment is aimed at reducing symp toms and signs. After a relative lull of almost 40 years, new drugs—tacrolimus and pimecrolimus—have appeared that offer different approaches to managing this miserable disease. Do they work? Are they safe? And how do they compare with existing treatments?